Sosialisasi tentang Nilai Integritas dalam Berwirausaha di SMA Negeri 1 Tanah Putih oleh Tim Forum Antikorupsi Provinsi Riau - Saputra, Hendra Eka; Widodo, Widodo (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The value of Integrity must be accepted by every human being. This is certainly a concrete manifestation of the history of the creation of humans on earth. These values are also applied in everyday life, including entrepreneurial activities. Therefore the community service team together with the Riau Province Anti-Corruption Extension Forum held socialization on the importance of the value of integrity in entrepreneurship. The method used is a case study at SMA Negeri 1 Tanah Putih with an implementation date of 18 August 2022. The target achieved is the understanding of SMA Negeri 1 Tanah Putih students who belong to the millennial generation who are dominantly working or entrepreneurship rather than continuing their education at tertiary institutions. Therefore, instilling the value of integrity is useful as a moral provision that must be applied by Tanah Putih 1 Public High School students in carrying out activities including entrepreneurship.